Blogging in the new normal using the WeCWI-enabled blogging manual: a pilot study / Boon Yih Mah and Hwei Chiet Cheah - Boon, Yih Mah; Hwei, Chiet Cheah (Universiti Teknologi MARA, 2002)
The COVID-19 outbreak has had an irreversible impact on education globally; students must be engaged in a digital environment for their learning process. They were encouraged or even forced to employ specific online learning tools and access a wide range of assigned digital instructional materials. A blog is one of the most popular Web 2.0 tools, while blogging is a favourable instructional and learning activity. However, limited educational resources on blogging are noticeable and can serve as instructional guidance for students. Hence, it needs to have a manual on creating a blog with one of the most popular blog hosts, Blogger.com, which serves as a reference to prepare the students to start blogging. Thus, a pilot study on creating blogs using Blogger.com was conducted with an intact class of 22 students from one of the Matriculation colleges in Kedah, Malaysia. Before collecting data for conducting a mixed-method study on the effectiveness of blogging, a pilot study using a survey on the use of a manual to create a blog as a WeCWI-enabled instructional tool in future research. After analysing the data from the respondents' feedback, it shows that students started their blogs effectively by independently referring to the instructor's directions. Students practise academic writing using blogs as a learning tool, resulting in a noticeable positive effect on self-perceived learning.